Financial Contagion in the 2007-2009 and Eurozone Debt Crises: Mostly Interdependence - To, Jeffrey (Université d'Ottawa | University of Ottawa, 2013)
This study employs a VECH-GARCH model to assess the effects of contagion during the 2007-2009 financial crisis. Weekly stock returns data for five Eurozone countries, the BRICs, and the United States between 2002 and 2013 were used. Several inferences can be drawn from this model. First, there was significant volatility clustering, both with respect to stock returns and bivariate correlations. Second, in the initial stage of both the 2007-2009 crisis and the Eurozone debt crisis, the U.S. stock market was less correlated with the European markets, as investors viewed news as country-specific. Conversely, there were no dynamic changes in correlations between the U.S. stock market returns and those of the BRICs. Third, during the Eurozone debt crisis, the Irish stock returns became slightly more correlated with the returns in other Euro countries, as the crisis was viewed as region-specific due to more integrated financial and trade linkages. Finally, there was strong evidence that quantitative easing increases correlations between international stock returns.